TIME SCALE AND CONDITIONS OF WEATHERING UNDER TROPICAL CLIMATE: STUDY OF THE AMAZON BASIN WITH U-SERIES - Dosseto A.; Bourdon B.; Gaillardet J.; Allegre C.J.; Filizola N. (My University, 2006)
The Rio Solimoes/Amazonas (Amazon River) and its major tributaries have been analyzed for U-series nuclides. 238U-234U -230Th-226Ra disequilibria have been measured in the dissolved (<0.2 ?m) and suspended loads (>0.2 ?m) as well as bed sands. U-series disequilibria are closely related to major and trace element compositions and therefore reflect elemental fractionation during chemical weathering. Moreover, while the dissolved load records present-day weathering, suspended particles integrate the erosion history over much longer time scales (>100 ka). Lowland rivers are characterized by long time scales of chemical erosion (?100 ka) resulting in a high weathering intensity. Moreover, exchange between suspended particles and the dissolved load may explain the U-series signature for these rivers. By combining U-series and Pb isotopes in suspended particles, we show that erosion in the Rio Madeira basin occurred as a multi-step process, whereby the pristine continental crust was eroded several hundreds of Ma ago to produce sediments that have then been integrated in the Cordillera by crustal shortening and are currently eroded. In contrast, recent erosion of a pristine crust is more likely for the Rio Solimoes/Amazonas (<10 ka). the suspended particles of rivers draining andes
Keywords: EROSION; TROPICAL ENVIRONMENT; URANIUM ISOTOPE; WEATHERING; AMAZON BASIN